MUNASABAH DALAM ULUMUL QUR’AN - Yudi Hardiyani (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Studying the munasabah of the Qur'an can be considered important, but in the development of the Qur'anic sciences, the science of munasabah of the Qur'an is a scientific discipline, sometimes it is studied, sometimes it is not. Because the issue of munasabah is included in the category of ikhtilafiyah , the rules are also ikhtilafiyah. the legendary Egyptian cleric Jalaluddin al-Suyuthi is one of the oldest 'Ulum Al-Qur'an writers. Al-Itqan Fi 'Ulum Al-Qur'an is the eternal witness of his most monumental work. Although this book has been less popular since his death, but the presence of al Suyuthi, who lived about two centuries later, made this work shine again and became a famous work through al Itqan fi Ulum Al-Qur'an. This paper describes the munasabah from the book Al-itqan Fi 'Ulum Al-Qur'an. This research model is entirely a literature study, in this case the primary data is the work of Master piece Al-Jalaluddin. Meanwhile, secondary data sources include other references written by intellectuals, either in the form of comments, analyzes or academic works. According to Al-Jalaluddin, munasabah is an attempt by human thought to explore the secret of the relationship between verses or letters that can be accepted by reason.